MEDIA EXPOSURE AS A GAME CHANGER: PANEL DATA ANALYSIS OF SUSTAINABILITY IMPACT ON FIRM VALUATION - Vanisa Ratna Sari; Hanifah, Umi; Suhatmi, Erna Chotidjah (Berkala Akuntansi dan Keuangan Indonesia, 2025)
This study analyzes the impact of Carbon Emission Disclosure (CED), Carbon Performance (CP), and Green Intellectual Capital (GIC) on firm value, with Media Exposure (ME) acting as a moderating variable. The research focuses on energy companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2024 period. Using panel data analysis, the Random Effect Model (REM) was identified as the most appropriate model after conducting Chow, Hausman, and Lagrange Multiplier tests, as well as classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation). The findings indicate that CED, CP, and GIC significantly influence firm value. However, Moderated Regression Analysis (MRA) revealed that ME only moderates the relationship between GIC and firm value, failing to moderate the effects of CED and CP. This suggests that media coverage concerning a company's green innovations and sustainability practices effectively enhances investor visibility and understanding of intangible assets, thereby contributing to positive perception and increased confidence.